STUDI KOMPARATIF KERAGAAN KEBUN KELAPA SAWIT POLA SWADAYA RSPO DAN NON-RSPO DI KECAMATAN UKUI KABUPATEN PELALAWAN - Hutabarat, Sakti; Yusri, Jumatri; ', Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Oil palm produces vegetable oil used in various products including food, non-food, and biodiesel. Increasing demand for crude palm oil has provoked demand for fresh fruit bunches. The oil palm growers respond the higher demand by development of new planting. Land expansion become an important issue since it creates not only positive impacts but also negative impacts such as deforestation, biodiversity loss, forest fire and land conflicts. RSPO certification was established to mitigate the negative impacts and to promote sustainable production of palm oil. The growers must comply the Principles and Criteria of RSPO. Independent smallholers are the most susceptible growers to be included in the oil palm supply chain. How does the farmers manage their plantation to meet the standard while they face various barriers to run their business? The aims of this study are to analyse smallholders’ performance, to assess the application of RSPO Principles and Criteria, and to compare productivity and farm income of oil palm plantations between the RSPO and non-certified independent smallholders. A survey method is used to collect data from the selected samples, 78 of RSPO-certified and 59 of Non-certified smallholders. Using quantitative and qualitative analyses, the result shows that the RSPO-certified smallholders have a very good performance and applied all the RSPO standard. The non-certified smallholders have a good performance and they are in the process of certification to meet the criteria. There are no significant differences in productivity and farm income between the two models. The RSPO-certified and non-certified smallholders located in the same area, therefore, most of the non-certified smallholders have seen the best practices and start applying some of the best practices by themselves.   Keywords: Certification, independent smallholders, productivity, farm income